Implementasi Teori Dakwah Fungsional dalam Meningkatkan Kesejahteraan Ummat - Saefuloh, Uwoh (Jurnal Ilmu Dakwah, 2009)
Daâwah is a changing process that orient to change a condition / society life situation to aim condition of its life the better. This mean that Daâi. constitute agent of social change that gets to build condition/ society life situation goodly and welfare. In consequence, in aplicate, daâwah processes ought to use theory and functional daâwah approach. Its mean, theory and also daâwah approach utilized is relevant with charge of society life reality that stipulates with charge ofÂ  the lives need. To it Alquran was laid a lot of practical bases dual with daâwah theory implementation which relevant with society reality as mad â uÂ  its relationship with ummah well-being step-up.